Infographic of benevolence practices: public sector's myth or reality / Nor Zaini Zainal Abidin ... [et al.] - Zainal Abidin, Dr Nor Zaini; Andin Salamat, Azni Syafena; Shawalludin, Syahrini; Abdul Rahman, Azlan; Yusoff, Dr Siti Norfazlina (2021)
Government has the responsibility to provide the best service to the people. Thus, accountability and integrity of government are important to ensure that the ruling government stays in power by gaining public trust. Consequently, a shortfall in these aspects will cause the ruling parties to lost public trust and eventually the national election. As a result, many conflicting issues arise especially in administration of service delivery. However, several challenges faced by the government can tarnish the confidence of public towards the public sector. Among the challenges are the accessibility of public goods, performance of service delivery, public servant's productivity, and bureaucracy. However, the roles and responsibilities of public servant must be carried out in the efficient and effective manner. Thus, there are many efforts done by the government to enhance the quality-ofservice delivery but, there are still issues on administrative and public expectation that led to public complaints and grievances. In line with this and as to minimize the occurrence and continuation of this dilemma, public sectors have come up with several key values on accountability and integrity. Accordingly, benevolence tends to be invisible as compared to other key values practicing in public sector. As such, the premise of this project is to develop infographic on benevolence practices, even the exercise of benevolence is seen as unrealistic or inevitable to secure public trust towards public sectors. This infographic is a simple and friendly platform to further describe on benevolence aspects. It will also serve as a guide to public sector. It helps to develop inner value of public servants in term of commitment, sense of urgency and honesty in delivering services. It is interesting to note that, the commercialization potential towards this infographic may provide platform for government agencies to have clear knowledge, skills, and abilities in determining the benevolence aspects that they need to carry out. Lastly, this infographic is useful to enhance intrinsic value of public servant to become more compassionate, trustworthy, and reliable to public needs.